LEVERAGING THE SCHOOL ENVIRONMENT AS A LEARNING MEDIUM TO CULTIVATE STUDENTS SOCIAL AWARNESS - wildan alfahmi; Lusty Firmantika (SOSIOEDUKASI, 2026)
The objective of this study is to describe social studies learning strategies based on Project-Based Learning utilizing the school’s surrounding environment to foster students social awareness. This study employed a qualitative case study design at SMPN 1 Wajak, involving the vice principal for curriculum, social studies teachers, the eight grade students from Class VIII G as informants. Data were collected through observations, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model. The results indicate that the utilization of physical and social environments such as rice fields, markets, and tourist attractions effectively support contextual learning through the preparation, implementation, and follow-up activities. These activities encourage active student engagement and foster a socially responsible character, demonstrated through empathy, cooperation, and concern for the surrounding environment. However, the implementation of this learning still faces challenges, including time constraints, varying levels of student participation, and limited supporting resources. Therefore, social studies instruction based on Project-Based Learning utilizing the surrounding environment of the school can serve as an effective strategy for fostering students’ socially responsible character.